Risk of progression of interstitial pneumonia with autoimmune features to a systemic autoimmune rheumatic disease. (24th September 2019) - Alevizos, Michail K; Giles, Jon T; Patel, Nina M; Bernstein, Elana J
Abstract: Objective: The aim of this study was to determine the risk of developing a systemic autoimmune rheumatic disease (ARD) after an initial diagnosis of interstitial pneumonia with autoimmune features (IPAF). Methods: We performed a retrospective cohort study of patients with interstitial lung disease (ILD) who were evaluated at Columbia University Irving Medical Center from 2009 to 2017. We divided patients with idiopathic ILD into two groups: those who met IPAF criteria and those who did not meet IPAF criteria at initial ILD diagnosis. We examined the association between IPAF and diagnosis of ARD during the follow-up period using a multivariable-adjusted logistic regression model. Results: Of the 697 patients with ILD who were screened, 174 met inclusion criteria (50 met IPAF criteria and 124 did not). During a median follow-up period of 5.2 years, 16% (8/50) of subjects with IPAF were diagnosed with an ARD compared with 1.6% (2/124) of subjects without IPAF ( P = 0.001). Adjusting for age, sex, smoking status and use of immunosuppressive therapy, the odds of progressing to an ARD were 14 times higher in subjects with IPAF than in those without IPAF (odds ratio 14.18, 95% CI 1.44–138.95, P = 0.02). Conclusion: The presence of IPAF confers an increased risk of developing an ARD. Patients with IPAF should therefore be followed closely for the development of an ARD.